Changing Social Security in Latin America Toward Alleviating the Social Costs of Economic Reform - Mesa-Lago, Carmelo (Lynne Rienner Publishers, 2023)
Mesa-Lago concentrates on the process of social security reform - intended to create mechanisms that can more effectively alleviate the severe social costs of economic restructuring and adjustment - in eight Latin American countries